THE ISSUE OF REDUCING METAL CONSUMPTION IN THE PRODUCTION OF HOT-ROLLED PIPES (Modern Problems of Metallurgy, 2025)
Resource and energy conservation, along with environmental safety, are the main historical areas of development for metallurgy in modern conditions. This article discusses the main areas of metal saving in the production of hot-rolled seamless pipes using various pipe rolling units, which have reached practical use. Reducing metal consumption is one of the main ways to reduce costs in pipe production, as the share of the cost of a given metal minus waste ranges from 50% to 85%. An increase in metal consumption is one of the main factors in reducing the company's competitiveness in the domestic and foreign markets. An analysis of metal consumption in the production of hot-rolled seamless pipes at various pipe rolling units has shown that the largest technological metal losses occur at pilgrim mills due to metal cut-off at the pilgrim mill into the billet and pilgrim head. The main directions of reducing these losses are considered, and it is noted that the most effective are rolling the liner into the joint and rolling the pilgrim head on a free section of the mandrel. One of the main reserves for reducing metal consumption during hot rolling is the manufacture of pipes with an average wall thickness close to the rolling nominal or within the field of negative tolerances. Reducing metal losses by improving pipe accuracy can be achieved by centring the liner on the mandrel before pilgrim rolling. To solve this problem, new processes for preparing the front and rear ends of the sleeves have been proposed. The article considers the issues of reducing scale formation during hot rolling of pipes by accelerating the cooling of the product with water at the outlet of a clean gauge and increasing the cooling rate in air. One of the new ways to prevent scale formation on the inner surface of the liner when it is pierced on a rolling mill is to supply deoxidiser through the hollow core of the mandrel directly during the piercing process. The known and new technical solutions considered in this paper can be used in the development of metal-saving technology
Keywords: hot-rolled pipe; billet; liner; pilgrim mill; piercing beam mill; pickling; piercing head; scale formation; metal saving; technological cut; metal consumption factor.